Negative electrode active material layer and sodium-ion battery
Patent Information
- Application Number
- JP2025061807
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2026-10-16
AI Technical Summary
【0009】 本開示によれば、負極活物質層の充電時における充電容量と膨張の抑制を両立させた負極活物質層、該負極活物質層を用いたナトリウムイオン電池、及び該負極活物質層の製造方法を提供することができる。
Smart Images

Figure 2026168593000001_ABST
Abstract
Description
[Technical Field]
[0001] This disclosure relates to a negative electrode active material layer and a sodium-ion battery. [Background technology]
[0002] Patent Document 1 discloses a non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, characterized in that the negative electrode uses an electrode in which a negative electrode material is filled with a current collector having a three-dimensional structure, the negative electrode material comprising a composite material consisting of a material containing an element capable of forming an alloy with lithium and a conductive material.
[0003] Patent Document 2 discloses a secondary battery that uses one type of negative electrode metal selected from the group consisting of alkali metals, alkaline earth metals, and aluminum as the negative electrode, and uses an oxide or sulfide or a mixture thereof as the positive electrode active material, wherein a porous aluminum body having a three-dimensional network structure is used as the positive electrode current collector. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2003-308831 [Patent Document 2] Japanese Patent Publication No. 2012-186160 [Overview of the project] [Problems that the invention aims to solve]
[0005] In sodium-ion batteries, when phosphorus-containing negative electrode active material particles are used, the negative electrode active material absorbs sodium ions and expands significantly during charging, resulting in a significant increase in the thickness of the negative electrode active material layer.
[0006] To suppress the increase in the thickness of the negative electrode active material layer, one possible approach is to reduce the content of negative electrode active material particles in the negative electrode active material layer. However, reducing the content of negative electrode active material particles may decrease the charging capacity of the negative electrode active material layer during charging.
[0007] The present disclosure aims to provide a negative electrode active material layer that achieves both high charging capacity and suppression of expansion during charging, a sodium-ion battery using the negative electrode active material layer, and a method for manufacturing the negative electrode active material layer. [Means for solving the problem]
[0008] The Disclosing Party has found that the above problem can be achieved by the following means: 《Aspect 1》 It contains a foamed metal layer and phosphorus-containing negative electrode active material particles. The negative electrode active material particles are supported in the voids of the foamed metal layer. The foamed metal layer has a polyhedral framework, and the smallest angle between two adjacent faces of the polyhedron is between 55° and 180°. Negative electrode active material layer. 《Aspect 2》 The negative electrode active material layer according to embodiment 1, wherein the smallest angle among the angles formed by two adjacent faces of the polyhedron is between 55° and 110°. 《Aspect 3》 The negative electrode active material layer according to embodiment 1 or 2, wherein the Young's modulus of the foamed metal layer is greater than the Young's modulus of the negative electrode active material particles. Appearance 4 A sodium-ion battery having a negative electrode active material layer, an electrolyte layer, and a positive electrode active material layer in the order described in any one of embodiments 1 to 3. Appearance 5 (A) Impregnating a foamed metal layer having a polyhedral skeleton with a slurry containing phosphorus-containing negative electrode active material particles and drying it, (B) The negative electrode active material layer is formed such that the smallest angle between two adjacent faces of the polyhedron is between 55° and 180°. A method for producing a negative electrode active material layer, comprising the steps in this order. Advantageous Effects of Invention
[0009] According to the present disclosure, it is possible to provide a negative electrode active material layer that achieves both high charge capacity during charging of the negative electrode active material layer and suppression of expansion, a sodium-ion battery using the negative electrode active material layer, and a method for producing the negative electrode active material layer. Brief Description of Drawings
[0010] [Figure 1] Figure 1 is a schematic diagram showing a skeleton 1 of a metal foam layer and negative electrode active material particles 2 in a negative electrode active material layer according to one embodiment of the present disclosure. [Figure 2] Figure 2 is a schematic diagram showing a skeleton 1 of a metal foam layer and negative electrode active material particles 2 in a negative electrode active material layer different from the embodiment of the present disclosure. [Figure 3] Figure 3 is a schematic diagram showing a skeleton 1 of a metal foam layer and silicon-based negative electrode active material particles 3 in a negative electrode active material layer further different from the embodiment of the present disclosure. [Figure 4] Figure 4 is a schematic diagram of a polyhedral structure 5 as a skeleton of a metal foam layer. [Figure 5] Figure 5 is a schematic diagram of a sodium-ion battery 100 according to one embodiment of the present disclosure. [Figure 6] Figure 6 is a graph showing the relationship between the dihedral angle (°) of the metal foam layer and the expansion rate of the negative electrode active material layer when sodium-ion batteries using the negative electrode active material layers of respective examples are charged and discharged. Modes for Carrying Out the Invention
[0011] Hereinafter, embodiments of the present disclosure will be described in detail. The present disclosure is not limited to the following embodiments, and can be implemented with various modifications within the scope of the gist of the disclosure.
[0012] 1. Negative Electrode Active Material Layer The negative electrode active material layer of this disclosure contains a foamed metal layer and phosphorus-containing negative electrode active material particles. The negative electrode active material particles are supported in the voids of the foamed metal layer. The foamed metal layer has a polyhedral framework, and the smallest angle between two adjacent faces of the polyhedron is between 55° and 180°.
[0013] For example, in a sodium-ion battery, we considered using a negative electrode active material layer in which phosphorus-containing negative electrode active material particles are supported in the voids of a conductive foamed metal layer.
[0014] From the perspective of improving the charge density of sodium-ion batteries, it is conceivable to reduce the thickness of the negative electrode active material layer by supporting negative electrode active material particles on a foamed metal layer and then pressing it. Phosphorus-containing negative electrode active material particles are generally soft and deform when pressed, becoming embedded in the bent parts of the metal framework of the foamed metal layer, that is, the corners formed by two adjacent faces of the polyhedral metal framework. In such a negative electrode active material layer, the negative electrode active material particles expand during charging and discharging, pushing open the bent parts of the metal framework of the foamed metal layer, resulting in expansion of the negative electrode active material layer. The expansion of phosphorus-containing negative electrode active material particles during charging is particularly large, so the expansion of the negative electrode active material layer is also significant.
[0015] In the anode active material layer of this disclosure, with respect to the foamed metal layer, the smallest angle between two adjacent faces of the polyhedral framework is between 55° and 180°. As shown in Figure 1, the angle between two adjacent faces of the polyhedral framework 1 is relatively large, making it difficult for the phosphorus-containing anode active material particles 2 to penetrate the bent portions of the foamed metal layer framework 1. Therefore, the bent portions of the foamed metal layer are less likely to be pushed out due to the expansion of the phosphorus-containing anode active material particles 2 during charging.
[0016] In contrast, as shown in Figure 2, when the smallest angle between two adjacent faces of the polyhedral skeleton 1 is less than 55°, the phosphorus-containing negative electrode active material particles 2 can easily penetrate the bent portion of the foamed metal layer skeleton 1, and the bent portion of the foamed metal layer is easily pushed open during charging.
[0017] As shown in Figure 3, when silicon-based active material particles 2, such as Si particles, are used as the negative electrode active material particles in a lithium-ion battery, the high rigidity of the silicon-based active material particles 2 makes it difficult for them to penetrate the bent portions of the foamed metal layer framework 1. However, the expansion of the silicon-based active material particles during charging destroys the foamed metal layer framework 1.
[0018] Therefore, the technical challenges of this disclosure should be recognized as being specific to configurations in which phosphorus-containing negative electrode active material particles are supported on a foamed metal layer, and particularly to sodium-ion batteries.
[0019] 1-1. Foamed metal layer The foamed metal layer used in the negative electrode active material layer of this disclosure has a polyhedral framework, and the smallest angle between two adjacent faces of the polyhedron is between 55° and 180°. Here, the framework of the foamed metal layer, that is, the structure of the pores of the foamed metal, is ideally a structure in which icosahedrons 5 are connected, as shown in Figure 5, and the metal framework is arranged on the edges.
[0020] The smallest angle between two adjacent faces of a polyhedron may be 55° or greater, 65° or greater, 75° or greater, or 85° or greater. This angle may be 180° or less, 150° or less, 110° or less, or 70° or less. It is particularly preferable that the smallest angle between two adjacent faces of a polyhedron be between 55° and 110°.
[0021] Examples of materials for the foamed metal layer include nickel or nickel alloys, iron, and stainless steel. These metals have a high Young's modulus, and even when the phosphorus-containing negative electrode active material particles expand during charging, the bent portion of the foamed metal layer is particularly resistant to stretching.
[0022] The Young's modulus of the foamed metal layer is preferably greater than that of the phosphorus-containing negative electrode active material particles. The Young's modulus of the foamed metal layer material is preferably 180 GPa to 250 GPa. The Young's modulus of the foamed metal layer material may be 180 GPa or more, 185 GPa or more, 190 GPa or more, or 195 GPa or more. The Young's modulus of the foamed metal layer material may be 250 GPa or less, 240 GPa or less, 230 GPa or less, 220 GPa or less, or 210 GPa or less.
[0023] The thickness of the foamed metal layer may be, for example, 0.45 mm to 1.5 mm. The thickness of the foamed metal layer may be 0.45 mm or more, 0.5 mm or more, 0.6 mm or more, 0.8 mm or more, or 0.9 mm or more. The thickness of the foamed metal layer may be 1.5 mm or less, 1.4 mm or less, 1.3 mm or less, or 1.2 mm or less.
[0024] 1-2.Negative electrode active material particles The negative electrode active material particles used in the negative electrode active material layer of this disclosure are negative electrode active material particles containing phosphorus.
[0025] The negative electrode active material particles can be, for example, phosphorus, more specifically red phosphorus, or phosphorus compounds. The negative electrode active material particles can be, for example, just phosphorus, or a composite material of phosphorus and carbon. Examples of phosphorus-carbon composite materials include, but are not limited to, a mixture of red phosphorus and acetylene black.
[0026] The phosphorus-containing negative electrode active material particles are preferably supported on a foamed metal layer. The basis weight of the negative electrode active material particles in the foamed metal layer is 5 mg / cm³. 2 ~50 mg / cm³ 2 This may be the case. The basis weight of the negative electrode active material particles in the foamed metal layer is 5 mg / cm³. 2 More than 10mg / cm 2 Above 15 mg / cm³ 2 The above is acceptable. The basis weight of the negative electrode active material particles in the foamed metal layer is 50 mg / cm³. 2 Below 40mg / cm 2 Below 30mg / cm2 or 20 mg / cm 2 or less.
[0027] 2. Sodium Ion Battery The sodium ion battery 100 of the present disclosure has, for example, a negative electrode current collector layer 10, the negative electrode active material layer 20 of the present disclosure, an electrolyte layer 30, a positive electrode active material layer 40, and a positive electrode current collector layer 50 in this order, as shown in FIG. 5. Here, when the negative electrode active material layer 20 and / or the positive electrode active material layer 40 uses a conductive material, for example, a foamed metal layer, the foamed metal layer can also serve as the current collector. In this case, the negative electrode current collector layer 10 and / or the positive electrode current collector layer 50 are optional components.
[0028] The sodium ion battery of the present disclosure may be a liquid-based sodium ion battery, specifically a sodium ion battery using an aqueous or non-aqueous electrolyte, or an all-solid sodium ion battery. Further, the sodium ion battery of the present disclosure may be a sodium ion secondary battery.
[0029] 2-1. Electrolyte Layer The electrolyte layer 30 is a layer formed between the negative electrode active material layer 20 and the positive electrode active material layer 40. The electrolyte layer 30 conducts ions between the positive electrode active material and the negative electrode active material via the electrolyte contained therein. The form of the electrolyte layer 30 is not particularly limited, and examples thereof include a liquid electrolyte layer, a gel electrolyte layer, and a solid electrolyte layer.
[0030] The liquid electrolyte layer is usually a layer formed using a non-aqueous electrolytic solution. The non-aqueous electrolytic solution usually contains a sodium salt and a non-aqueous solvent. Examples of the sodium salt include inorganic sodium salts such as NaPF₆, NaBF₄, NaClO₄ and NaAsF₆; and organic sodium salts such as NaCF₃SO₃, NaN(CF₃SO₂)₂, NaN(C₂F₅SO₂)₂, NaN(FSO₂)₂, and NaC(CF₃SO₂)₃.
[0031] The non-aqueous solvent is not particularly limited as long as it can dissolve sodium salts. For example, high dielectric constant solvents include cyclic esters (cyclic carbonates) such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC), as well as γ-butyrolactone, sulfolane, N-methylpyrrolidone (NMP), and 1,3-dimethyl-2-imidazolidinone (DMI). On the other hand, low viscosity solvents include linear esters (linear carbonates) such as dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC), as well as acetates such as methyl acetate and ethyl acetate, and ethers such as 2-methyltetrahydrofuran. A mixed solvent containing both a high dielectric constant solvent and a low viscosity solvent may also be used.
[0032] The concentration of sodium salt in the non-aqueous electrolyte is preferably in the range of 0.3 mol / L to 5 mol / L, and more preferably in the range of 0.8 mol / L to 1.5 mol / L. This is because if the sodium salt concentration is too low, a decrease in volume may occur at high rates, and if the sodium salt concentration is too high, viscosity will increase, which may cause a decrease in volume at low temperatures. In addition, a low-volatility liquid such as an ionic liquid may be used as the non-aqueous electrolyte.
[0033] A gel electrolyte layer can be obtained, for example, by adding a polymer to a non-aqueous electrolyte and causing gelation. Specifically, gelation can be achieved by adding a polymer such as polyethylene oxide (PEO), polyacrylonitrile (PAN), or polymethyl methacrylate (PMMA) to a non-aqueous electrolyte.
[0034] The solid electrolyte layer is a layer made of a solid electrolyte. The solid electrolyte is not particularly limited as long as it has Na ion conductivity, but examples include the above-mentioned NaMH compounds, known oxide solid electrolytes and sulfide solid electrolytes.
[0035] 2-2. Positive electrode active material layer The positive electrode active material layer 40 contains at least positive electrode active material. Furthermore, it may optionally contain conductive materials, binders, and solid electrolytes. These materials may be those commonly used in sodium-ion batteries.
[0036] 2-3. Current collector layer Typically, a positive electrode current collector layer 50 is placed on the side of the positive electrode active material layer 40 that is not facing the electrolyte layer 30. Examples of materials for the positive electrode current collector layer 50 include SUS, aluminum, nickel, iron, titanium, and carbon. Examples of shapes for the positive electrode current collector layer 50 include foil, mesh, and porous forms. A positive electrode can be easily manufactured by laminating the positive electrode current collector 50 onto the positive electrode active material layer 40 described above. However, depending on the materials contained in the positive electrode active material layer 40, the positive electrode current collector layer 50 may be omitted. In this case, the positive electrode active material layer 40 itself becomes the positive electrode.
[0037] The negative electrode active material layer 20 typically has a negative electrode current collector layer 10 on the side of the negative electrode active material layer 20 that is not on the side facing the electrolyte layer 30. Examples of materials for the negative electrode current collector layer 10 include SUS, aluminum, nickel, copper, and carbon. Examples of shapes for the negative electrode current collector layer 10 include foil, mesh, and porous shapes. A negative electrode can be easily manufactured by laminating the negative electrode current collector layer 10 onto the negative electrode active material layer 20 described above. However, since the negative electrode active material layer 20 of this disclosure has a foamed metal layer, the negative electrode current collector layer 10 may be omitted.
[0038] 2-3. Other Configurations A general-purpose battery case can be used for the sodium-ion battery 100, and is not particularly limited. Furthermore, the sodium-ion battery 100 may be a primary battery or a secondary battery, but it is preferable to use a secondary battery in order to more effectively demonstrate the effect of improving durability.
[0039] 3. Method for manufacturing the negative electrode active material layer The method for manufacturing the negative electrode active material layer of this disclosure is as follows: (A) Impregnating a foamed metal layer having a polyhedral skeleton with a slurry containing phosphorus-containing negative electrode active material particles and drying it, (B) The negative electrode active material layer is formed such that the smallest angle between two adjacent faces of the polyhedron is between 55° and 180°. It has them in this order.
[0040] 3-1.Process A Step A involves impregnating a foamed metal layer having a polyhedral structure with a slurry containing phosphorus-containing negative electrode active material particles, and then drying it.
[0041] The slurry can be one in which phosphorus-containing negative electrode active material particles are dispersed in an organic solvent. For example, N-methylpyrrolidone (NMP) can be used as the organic solvent.
[0042] Impregnation of the foamed metal layer with slurry may be carried out by known methods, such as coating or immersion.
[0043] 3-2.Process B Step B involves pressing a foamed metal layer in the thickness direction of the foamed metal layer so that the smallest angle between two adjacent faces of the polyhedron is between 55° and 180°, thereby forming the negative electrode active material layer. If the smallest angle between two faces of the foamed metal layer used in Step A is between 55° and 180°, then, for example, Step B may be terminated without pressing.
[0044] The smallest angle between two adjacent faces of a polyhedron can be calculated, for example, from the ratio of the foamed metal layer to its thickness before pressing and the shape of the polyhedron.
[0045] For example, if we consider the framework of the foamed metal layer, that is, the structure of the holes in the foamed metal, as a structure of connected icosahedrons 5 as shown in Figure 5, then the angle between two adjacent faces of the polyhedron, i.e., the dihedral angle, is approximately 138°. Therefore, when the foamed metal layer is pressed to two-thirds of its original thickness, the minimum dihedral angle is calculated to be 92°.
[0046] 3-3. Other processes The process may further involve vacuum drying the foamed metal layer after step B. Vacuum drying may be carried out for, for example, 12 to 36 hours, preferably 24 hours, at 100°C to 200°C, preferably 120°C. [Examples]
[0047] 4. Examples 4-1. Examples 1-4 and Comparative Example 1 4-1-1. Example 1 Red phosphorus (high-purity chemical) and acetylene black (Li-400, DENKA) were used as raw materials, weighed in a mass ratio of 7:3 to a total of 5g. After mixing these in a mortar, they were placed in a ball mill pot along with 96g of φ5 zirconia balls, purged with Ar gas, sealed, and subjected to ball milling to obtain a P / C composite material. The ball milling conditions were 500 rpm for 24 hours.
[0048] The obtained P / C composite material was weighed in a mass ratio of P / C composite material:CNT:PVDF = 93:1:6 and dispersed and mixed in NMP to form a slurry. This slurry was applied to a 1.2 mm thick layer of foamed Ni (Celmet, Sumitomo Electric) and dried. It was then vacuum-dried overnight at 120°C to prepare the sample electrode. The basis weight of the P / C composite material on the foamed Ni was 10 mg / cm². 2 This electrode was evaluated using a CR2032 coin cell.
[0049] A metallic sodium foil was used as the counter electrode. 1M NaPF6 (EC:DEC=1:1vol, FEC3wt%) was used as the electrolyte. Evaluation was performed in a 25°C constant temperature bath at a voltage range of 0.01–2.0V and a C rate of 0.1C. The battery's charging capacity was calculated based on the mass of phosphorus in the electrode. In this experiment, the reaction in which phosphorus absorbs sodium is called charging, and the reaction in which sodium is desorbed is called discharging.
[0050] The electrode thickness before and after the initial charge was measured using a constant-pressure thickness gauge (Teclock, PG-15A), and the electrode expansion rate was calculated. The expansion rate is shown as a ratio with the thickness before the initial charge set to 1.00.
[0051] 4-1-2. Examples 2-4 and Comparative Example 1 For Examples 2-4 and Comparative Example 1, before vacuum drying, the 1.2 mm thick foamed Ni was pressed to the following thicknesses to adjust the smallest angle between two adjacent faces of the foamed Ni framework. Ideally, the foamed Ni framework, i.e., the pores, are a structure of connected icosahedrons as shown in Figure 5. The dihedral angle of a regular icosahedron is approximately 138°. Example 2: Foamed Ni thickness = 0.80 mm, dihedral angle = 92° Example 3: Foamed Ni thickness = 0.60 mm, dihedral angle = 69° Example 4: Foamed Ni thickness = 0.48 mm, dihedral angle = 55° Comparative Example 1: Foamed Ni thickness = 0.40 mm, dihedral angle = 46°
[0052] 4-2.Results The results are summarized in Table 1 and Figure 6.
[0053] [Table 1]
[0054] Table 1 and Figure 6 show that in Examples 1-4, where the dihedral angle was 55° or greater, the expansion rate was 1.22 (Example 4) or less. In contrast, in Comparative Example 1, where the dihedral angle was 46°, the expansion rate was 1.67, and the thickness of the negative electrode active material layer increased significantly after charging. [Explanation of symbols]
[0055] 1. Skeleton 2 Phosphorus-containing negative electrode active material particles 3. Silicon-based negative electrode active material particles 5 Polyhedral structure 10. Negative electrode current collector layer 20 Negative electrode active material layer 30 Solid electrolyte layer 40 Cathode active material layer 50 Positive electrode current collector layer 100 sodium-ion batteries
Claims
1. It contains a foamed metal layer and phosphorus-containing negative electrode active material particles. The negative electrode active material particles are supported in the voids of the foamed metal layer. The foamed metal layer has a polyhedral framework, and the smallest angle between two adjacent faces of the polyhedron is between 55° and 180°. Negative electrode active material layer.
2. The negative electrode active material layer according to claim 1, wherein the smallest angle among the angles formed by two adjacent faces of the polyhedron is between 55° and 110°.
3. The negative electrode active material layer according to claim 1, wherein the Young's modulus of the foamed metal layer is greater than the Young's modulus of the negative electrode active material particles.
4. A sodium-ion battery having a negative electrode active material layer, an electrolyte layer, and a positive electrode active material layer in that order, according to any one of claims 1 to 3.
5. (A) Adhering a slurry containing phosphorus-containing negative electrode active material particles to a foamed metal layer having a polyhedral skeleton and drying it, (B) The negative electrode active material layer is formed such that the smallest angle between two adjacent faces of the polyhedron is between 55° and 180°. A method for manufacturing a negative electrode active material layer having the following elements in this order.
Citation Information
Patent Citations
Nonaqueous secondary battery
JP2003308831A
Battery
JP2012186160A